A new type of headache, headache associated with airplane travel: Preliminary diagnostic criteria and possible mechanisms of aetiopathogenesis - Berilgen, M. Said; Muengen, Bulent (Sage Publications Ltd, 2011)
Background: In recent years, there has been an increase in the reports indicating a form of headache that occurs during commercial aircraft travel. This headache, called airplane headache by some authors, is believed to be a new type of headache. The headache has very specific characteristics and all of the cases exhibited very stereotypical symptoms. Methods: The headache starts suddenly during the ascent and/or descent of the commercial aircraft. It has a mean duration of 20 minutes, which is usually unilateral and commonly localized to periorbital region. The headache is described to be severe, and has a stabbing or jabbing nature, and generally subsides in a short time. In some cases, an organic cause can be identified whereas in others no organic pathology could be found. Results and conclusion: We described the clinical features of 22 cases who suffered from a headache that occurred during airplane travel. We examined other cases with similar features reported in the literature and proposed preliminary diagnostic criteria for this new form of headache. We also discussed the possible patholophysiological mechanisms that may cause this headache.
Keywords: Airplane travel; headache